Organic Isocyanates and Isothiocyanates: Versatile Intermediates in Agrochemistry - Lamberth, Clemens (Synthesis, 2021)
In recent decades, organic isocyanates and isothiocyanates have been often applied as reactive intermediates in research syntheses or manufacturing routes of many agrochemicals. These heterocumulenes allowed the installation of crucial carboxylic functions, such as carbamates, ureas, and semicarbazones, but have also been used for the construction of five- and six-membered heterocycles, such as tetrazolones, thiazoles, and uracils.1 Introduction2 Preparation of Carboxylic Acid Functions3 Preparation of Heterocyclic Rings4 Conclusion
Keywords: isocyanate; isothiocyanate; herbicide; fungicide; insecticide; agrochemical